Weibliche Personenbezeichnungen in der dänischen Gegenwartssprache - Rajnik, Eugeniusz (Katedra Skandynawistyki UAM, 2010)
Der Beitrag setzt sich vor allem zum Ziel, die Rolle der movierten Personenbezeichnungen im Sprachsystem zu analysieren und Kriterien für ihre Klassifikation zu erarbeiten. Im Mittelpunkt dieser Untersuchung stehen die morphologische Regelhaftigkeit, Häufigkeit des Vorkommens, die Beschränkungen der Movierung und die Regeln sowie Tendenzen der Verwendung von weiblichen Formen in der dänischen Gegenwartssprache.

The article reviews various definitions of Movierung in contemporary Danish, i.e. the formation of feminine nouns denoting people from respective masculine forms by means of productive and non-productive suffixes. The author discusses their use and various types of restrictions regarding their use, and points out feminine forms existing despite the lack of respective masculine forms. In addition, another way of forming feminine forms has been presented, including forms with -dame, -frue, -kone, -kvinde and -pige.
Keywords: Movierung; Movierte Bildung; Weibliche Personenbezeichnungen